2020
DOI: 10.5194/gmd-13-4773-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ice thickness distribution discretization on the sea ice concentration variability in the NEMO3.6–LIM3 global ocean–sea ice model

Abstract: Abstract. This study assesses the impact of different sea ice thickness distribution (ITD) discretizations on the sea ice concentration (SIC) variability in ocean stand-alone NEMO3.6–LIM3 simulations. Three ITD discretizations with different numbers of sea ice thickness categories and boundaries are evaluated against three different satellite products (hereafter referred to as “data”). Typical model and data interannual SIC variability is characterized by K-means clustering both in the Arctic and Antarctica be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…These results are consistent with previous work indicating that thinnest categories are most sensitive to thermodynamic processes, while thickest categories are most sensitive to dynamic processes (Hunke, 2014;Moreno-Chamarro et al, 2020). We expect the impact of higher ITD category resolution to decrease over time as Arctic sea ice becomes thinner on average, as demonstrated by the results of the future scenario SSP3-7.0.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with previous work indicating that thinnest categories are most sensitive to thermodynamic processes, while thickest categories are most sensitive to dynamic processes (Hunke, 2014;Moreno-Chamarro et al, 2020). We expect the impact of higher ITD category resolution to decrease over time as Arctic sea ice becomes thinner on average, as demonstrated by the results of the future scenario SSP3-7.0.…”
Section: Discussionsupporting
confidence: 91%
“…Massonnet et al (2011) found that increasing the number of ITD categories improved the seasonal to interannual variability of Arctic sea ice extent and retreat at basin-scales. In contrast, Moreno-Chamarro et al (2020) found that increasing the number of thin categories resulted in poorer comparisons of Arctic sea ice concentration and extent with observations when all other model settings were kept constant. Massonnet et al (2019) more broadly investigated the impact of the discretization and resolution of thick ice categories on representation of sea ice over the historical period.…”
mentioning
confidence: 80%
“…11l), with several lines clearly being outliers, which were checked to match jpl = 1. This is because the multi-category sea ice thickness takes into account the subgrid-scale variations in sea ice properties (Thorndike et al, 1975;Massonnet et al, 2019;Moreno-Chamarro et al, 2020) and is therefore significantly different from the singlethickness category (jpl = 1). For instance, the presence of thin sea ice categories in multi-category sea ice schemes al-lows for greater melt rates compared to a single-category scheme (Uotila et al, 2017).…”
Section: Key Parameters and Their Physical Effectsmentioning
confidence: 99%
“…9l), with several lines being clearly outliers, which were checked to match jpl=1. This is because the multi-category sea ice thickness takes into account the subgrid-scale variations in sea ice properties (Thorndike et al, 1975;Massonnet et al, 2019;Moreno-Chamarro et al, 2020) and is therefore significantly different from the single thickness category (jpl=1). For instance, the presence of thin sea-ice categories in multi-category sea-ice schemes allows for greater melt rates compared to a single-category scheme (Uotila et al, 2017).…”
Section: Key Parameters and Their Physical Effectsmentioning
confidence: 99%